Introducing an Arabidopsis thaliana Thylakoid Thiol/Disulfide-Modulating Protein Into Synechocystis Increases the Efficiency of Photosystem II Photochemistry - Wessendorf, Ryan L.; Lu, Yan (Frontiers in Plant Science, 2019)
Photosynthetic species are subjected to a variety of environmental stresses, including suboptimal irradiance. In oxygenic photosynthetic organisms, a major effect of high light exposure is damage to the Photosystem II (PSII) reaction-center protein D1. This process even happens under low or moderate light. To cope with photodamage to D1, photosynthetic organisms evolved an intricate PSII repair and reassembly cycle, which requires the participation of different auxiliary proteins, including thiol/disulfide-modulating proteins. Most of these auxiliary proteins exist ubiquitously in oxygenic photosynthetic organisms. Due to differences in mobility and environmental conditions, land plants are subject to more extensive high light stress than algae and cyanobacteria. Therefore, land plants evolved additional thiol/disulfide-modulating proteins, such as Low Quantum Yield of PSII 1 (LQY1), to aid in the repair and reassembly cycle of PSII. In this study, we introduced an Arabidopsis thaliana homolog of LQY1 (AtLQY1) into the cyanobacterium Synechocystis sp. PCC6803 and performed a series of biochemical and physiological assays on AtLQY1-expressing Synechocystis. At a moderate growth light intensity (50 µmol photons m-2 s-1), AtLQY1-expressing Synechocystis was found to have significantly higher Fv/Fm, and lower nonphotochemical quenching and reactive oxygen species levels than the empty-vector control, which is opposite from the loss-of-function Atlqy1 mutant phenotype. Light response curve analysis of PSII operating efficiency and electron transport rate showed that AtLQY1-expressing Synechocystis also outperform the empty-vector control under higher light intensities. The increases in Fv/Fm, PSII operating efficiency, and electron transport rate in AtLQY1-expressing Synechocystis under such growth conditions most likely come from an increased amount of PSII, because the level of D1 protein was found to be higher in AtLQY1-expressing Synechocystis. These results suggest that introducing AtLQY1 is beneficial to Synechocystis.